Exploring the multimodal role of Cnicus benedictus extract in the modulation of growth, hematobiochemical, histopathological, antioxidative performance, and immune-related gene expression of Oreochromis niloticus challenged with Aeromonas hydrophila - Salah, Abdallah S.; El-Nagar, Sahar H.; Elsheshtawy, Ahmed; Al-Dhuayan, Ibtesam; Fouad, Alamira Marzouk; Alnamshan, Mashael M.; Kadira, Hossam I.; Alaqeel, Nouf K.; El-Shobokshy, Set A.; Shukry, Mustafa; Abd-Elhafeez, Hanan H. (Frontiers in Marine Science, 2022)
This study explored the growth efficiency and the intracellular pathways by which Cnicus benedictus extract (CBE) acts. It investigated the antioxidant effects and efficacy of CBE as a fish supplement in attenuation of Aeromonas hydrophila in Oreochromis niloticus fish. Mono-sex Nile tilapia fish (n = 225) were randomly allocated to five groups in triplicate aquaria (n = 3 tanks per group, 15 fish per tank, with 120 L of water per tank) with a daily water exchange rate of 20%. After adaption for 2 weeks and body weight measuring, the experimental groups were fed isonitrogenous and isocaloric diets with different dosages of the ethanolic extract of C. benedictus for 10 weeks. The five groups were identified as the control group (CBE0.0), which was fed on the basal diet, while the second (CBE0.1), the third (CBE0.2), the fourth (CBE0.4), and the fifth (CBE0.6) groups were fed the basal diet supplemented with 0.1%, 0.2%, 0.4%, and 0.6% of C. benedictus extract, respectively. After the 10-week feeding trial was completed, the fish were inoculated with the PCR-identified pathogenic A. hydrophila in a challenge trial which lasted 15 days. A. hydrophila, one of the septicemic bacteria, causes severe economic losses, high mortality rates, and hemorrhages in Nile tilapia and other cultured freshwater fishes worldwide. The CBE was found to significantly increase the body mass, weight gain, and the specific growth rate, as well as the protein efficiency ratio of the fish. Increased survival percentage, accompanied by post challenge lymphocytosis with decreased liver enzyme levels, increased total protein, and improved kidney function markers were also seen. Additionally, CBE supplementation showed significant increases in phagocytic activity, phagocytic index, and lysosomal activity post challenge, accompanied by increases in antioxidant activity and the mRNA expression of cytokines genes hsp70 and tlr7 mRNA. The desirable effects of CBE treatment were confirmed by a histopathological examination of the height of intestinal villi and enterocytes lining the middle intestine and increases in the size of liver cells. We conclude that CBE increases the growth performance and modulates the antioxidant, inflammatory, stress, and immune-related genes in Nile tilapia. Moreover, the dietary inclusion of 0.42–0.47% CBE showed a better protective effect with the A. hydrophila challenge.